Local snake fruit conservation in East Java, Indonesia: Community knowledge and appreciation - Novita Indah; SERAFINAH INDRIYANI; ESTRI LARAS ARUMINGTYAS; RODIYATI AZRIANINGSIH (Society for Indonesian Biodiversity, 2021)
Abstract. Indah NK, Indriyani S, Arumingtyas EL, Azrianingsih R. 2021. Local snake fruit conservation in East Java, Indonesia: Community knowledge and appreciation. Biodiversitas 22: 416-423. The community-based conservation of plant species diversity by variety of utility is an effective method for preserving local plants. Salak or the ‘snake fruit’ from East Java is an important fruit plant species in East Java. However, recent dramatic decline in its production and consumption occurred due to land-use change of plantation into resident or settlement areas. This study aims to analyze the value of local knowledge and appreciation and discusses the conservation strategy to cope with the situation. This descriptive research adopted 328 respondents from 10 local and introduced snake fruit cultivation areas in East Java. Respondents were divided into four age categories: young (17-30 years), adults (30-45 years), middle-aged (45-60 years), and old (>60 years). The questioner consisted of closed and open questions about knowledge (9 questions) and appreciation (13 questions). There were variations in the level of knowledge and appreciation between locations and ages. The highest appreciation about snake fruit utilization was shown by the middle-aged group (85.53% and 75% respectively) based on the age group. In comparison, the lowest scores were shown in the young group (79.82% and 59.80% respectively). The points that support appreciation such as benefits  and value of snake fruit for societal support. Based on the snake fruit cultivation area, the highest score for knowledge and appreciation of its value was found in Bojonegoro (98.1% and 87.01% respectively) while these were the lowest in Trenggalek (68.0% and 57.10% respectively). Appreciation supports community-based conservation through snake fruit festivals, product diversification i.e. making processed foods, and its use in religious ceremonies.